Absence of Hall effect due to Berry curvature in phase space - Takehito Yokoyama (Nature Portfolio, 2021)
Abstract Transverse current due to Berry curvature in phase space is formulated based on the Boltzmann equations with the semiclassical equations of motion for an electron wave packet. It is shown that the Hall effect due to the phase space Berry curvature is absent because the contributions from “anomalous velocity” and “effective Lorentz force” are completely cancelled out.